Medicinal plants of Bangladesh and West Bengal : botany, natural products, & ethnopharmacology - Wiart, Christophe (Boca Raton, Florida : CRC Press, 2019)
MedicinalPlants of Bangladesh and West Bengalis a complete compendium. It provides the scientific name, classification, local name(s), historical background, local medicinal uses, botanical description, chemical constituents, pharmacological activity and toxicology of more than 100 medicinal spices used in Bengal. Chemical structures of active constituents are provided as well as numerous references. This book is an indispensabletool for researchers, as well as graduates in various disciplines, including pharmacy, pharmacology, medicine, biotechnology, nutrition, cosmetology and drug development. It is alsosuitable for anyone who islooking for natural products as leads to be developed in therapeutics, functional nutrition or cosmetology. Focuses on a group of herbs with economic importance - the spices. These herbs demonstrate the richness of chemical diversity and potential pharmacological applications Features field photos with local healers, markets and mode of preparation as well as providing a complete monograph for each plant Discusses the collection and observation of each medicinal spice and presents the ethnopharmacology recorded by the author in Bengal Provides a wealth of scientific information on medicinal spices from an expert in the field Fills an important niche due to the increasing global interests in natural foods and botanical drugs
OCLC-licensed vendor bibliographic record.
Keywords: Medicinal plants -- Bangladesh; Medicinal plants -- India -- West Bengal; Materia medica, Vegetable -- Bangladesh; Materia medica, Vegetable -- India -- West Bengal; MEDICAL / Pharmacology; SCIENCE / Chemistry / General; SCIENCE / Life Sciences / Botany